Differential Precipitation of Mg(OH)(2) from CaSO(4)·2H(2)O Using Citrate as Inhibitor—A Promising Concept for Reagent Recovery from MgSO(4) Waste Streams - Ziegenheim, Szilveszter (Molecules, 2020)
In hydrometallurgical processing and acidic wastewater treatment, one of the neutralizing agents employed is MgO or Mg(OH)(2). At the end of this process, the resulting solution, which is rich in SO(4)(2−) and Mg(2+) is treated with lime to remove (or minimize the amount) of these ions via the precipitation of Mg(OH)(2) and CaSO(4)·2H(2)O (gypsum). In our work, an attempt was made to separate the two solids by increasing the induction time of the gypsum precipitation, thus regenerating relatively pure Mg(OH)(2) which could be reused in wastewater treatments or hydrometallurgical processing circuits, and in this way, significantly enhancing the economic viability of the process. During our experiments, the reaction of an MgSO(4) solution with milk of lime prepared from quicklime was studied. The effects of a range of organic additives, which can slow down the precipitation of gypsum have been assessed. The process was optimized for the most promising inhibiting agent—that is, the citrate ion. The reactions were continuously monitored in situ by conductometric measurements with parallel monitoring of solution pH and temperature. ICP-OES measurements were also carried out on samples taken from the reaction slurry. The composition of the precipitating solids at different reaction times was established by powder XRD and their morphology by SEM. Finally, experiments were carried out to locate the additive after the completion of the precipitation reaction to get information about its potential reuse.